The Archean deep-marine environment: turbidite architecture of the Burwash Formation, Slave Province, Northwest Territories - Ferguson, Mark E; Waldron, John WF; Bleeker, Wouter (Canadian Journal of Earth Sciences, 2005)
The Slave Province is an Archean craton that contains an unusually large proportion of preserved sedimentary rock, including thick turbidite successions. The Burwash Formation is exposed in the southern Slave Province between the Anton and Sleepy Dragon basement massifs. At the base of the succession, volcanics and clastic metasedimentary rocks of the Raquette Lake Formation record initiation of the basin in a rifted arc environment. These are overlain by thin black slates representing a transgression, followed by well over 5 km of Burwash Formation metamorphosed turbiditic sandstones and slates interspersed with thin felsic tuff layers. Lateral correlation within the formation is possible using airphotos and recognizable tuff units. Burwash Formation sandstones include thinly bedded units displaying Bouma sequences and thicker bedded units with scour-and-fill structures and stratification bands, characteristic of dense sediment gravity flows. The sedimentary rocks are organized in architectural elements that include channel-fill sandstones and conglomerates, muddy levees, interchannel sandstones resembling high-amplitude reflection packages (HARPs) described from modern fans, and possible depositional lobes. The overall sedimentary architecture was probably controlled by events in the tectonically active source area or areas. The Archean turbidites resemble their Phanerozoic and modern analogues, although they show less voluminous levees, and are generally less organized, than large modern passive-margin fans, which probably have no equivalents in the Archean.